THE INFLUENCE OF SCOUT’S PERSPECTIVE OF THE COEXISTENCE OF GOOD AND EVIL TOWARDS HER CHARACTER DEVELOPMENT IN HARPER LEE’S TO KILL A MOCKINGBIRD - Anisa Qoiriani (Humaniora Scientia, 2020)
The objective of this article is to understand the influence of the main character, Scout Finch’sperspective of the coexistence of good and evil toward her character development in HarperLee’s novel entitled To Kill a Mockingbird. The writer applied library research to analyze thefindings. Some theories used to analyze the data are Discrimination, Post-structuralism, andPsychosocial. Moreover, the approaches used in this research are sociological approach,psychological approach, and post-structuralism approach. Good and evil do coexist in societyand witnessed by a child named Scout Finch. She is a White who lives within a racismneighborhood towards Black people. As a child of a White lawyer, Scout grows excellently evenwithout a presence of a mother. Some events happen that make her question about definition ofgood and evil. It develops Scout’s perspective towards the coexistence of good and evil thatinfluence her character development.